Pengembangan Bandara Udara, dampaknya dalam Peningkatan Wisata Halal dan Wisata Muslim di Indonesia - M. Ikhsan Setiawan; Agus Sukoco; Tubagus Purworusmiardi; Muh. Barid Nizaruddin Wajdi; Nuning Kurniasih (Sekolah Tinggi Agama Islam At-Tahdzib, Ngoro, Jombang, Indonesia, 2017)
Air transportation is increasingly important. seen in 2016, 835.9 thousand departures of domestic and international aircraft, 99.7 million domestic and international passengers, 75.6% load-factor domestic and international passengers, and 715.8 thousand tons of domestic and international goods are transported. The development of regional tourism is greatly helped by the availability of air transport infrastructure and commercial property. in 2016 the number of foreign tourists reached 11,519 million tourists, supported by 2,387 star hotels, with a five-star hotel room occupancy rate reached 54.34%. Indonesia as the largest Muslim population in the world certainly has many halal tourist destinations and Muslim tours. Increasing the quality of air transport and airport will automatically increase the interest of halal tourism and Muslim tours of Indonesia. so that the Muslim tourists and the world's halal tourists will visit many tourist destinations in Indonesia.